An overview of cast hot press forming die materials - S. N., Aqida (2014)

(untitled)
In the automotive industry, die life is an important factor due to its high cost and involvement in production lost, die blocks fabrication, maintenance and handling. Die materials require high thermal conductive properties to produce fast cooling of components. Major problem lies on die materials lifetime due to reduced thermal wear resistance when repeatedly heated and cooled.